История Англии эпохи Тюдоров в оценках исследователей Украины (XIX – начало ХХ вв.) - Лиман, С. И. (Давнина. Харківський історико-археологічний щорічник, 2016)
РезюмеЛиман С. І. Історія Англії доби Тюдорів в оцінках дослідників України (XIX—початок XX ст.)Науковий інтерес до історії Англії доби Тюдорів зберігався в Україні протягом усього розглянутого періоду. Цей інтерес підсилився з другої половини XIX ст., що варто зв’язувати, насамперед, з пошуками вченими історичних аналогій розвитку тюдорівської Англії та післяреформеної Росії. У роботах істориків України були порушені всі ключові аспекти розвитку тюдорівської Англії: внутрішньополітичні, зовнішньополітичні, соціально-економічні, конфесіональні, культурні, почасти правові. Найбільший внесок у вивчення історії епохи Тюдорів зробили В. Г. Авсєєнко (суспільно-політична і літературна діяльність Томаса Мора), О. І. Булгаков (догматична сутність англіканства), Г. О. Афанасьєв (ірландський і шотландський вектори політики Тюдорів), Є. В. Тарле (соціально-економічні реалії Англії XVI ст. як головне джерело формування суспільних поглядів Томаса Мора), К. О. Кузнєцов (боротьба палати общин за збільшення судових прав). Ці та деякі інші вчені України зробили вагомий внесок у вивчення історії тюдорівської Англії в рамках загальноросійської історіографії.Ключові слова: Англія, Тюдори, історія, історіографія, Томас Мор. SummaryS. Liman. History of Tudor england in Research of ukrainian scientists (19th — early 20th centuries)Tudor period in English history interested Ukrainian scientists during the whole period under question. This interest grew in the second half of 19th century as scientists first of all tried to find historical analogies between Tudor England and post-reform Russia. Ukrainian historians studied all key development aspects of Tudor England: inner and foreign policy, social and economic situation, religion, culture and, to some degree, legal issues. The most substantial contribution to the study of Tudors was brought by V. G. Avseenko (Thomas More’s public, political and literary activities), A. I. Bulgakov (dogmatic essence of Anglican Church), G. E. Afanasiev (Tudors policy in Scotland and Ireland), E. V. Tarle (English social and economic actualities in 16th century as basi source of Thomas More’s public view formation), K. A. Kuznetsov (House of Commons fight for extension of its judicial rights under Tudors and Stuarts). These and several other Ukrainian scholars greatly enriched the study of Tudor England history within the frames of all-Russian Empire historiography.Key words: England, Tudors, history, historiography, Thomas More.